From Subaltern to Subject: Women's Struggle Against Patriarchy in North Country (2005) - Sa’adah, Zumrotus; Nurhamidah, Idha; Muna, Nailil; Praptawati, Destary (Journal of English Language and Education, 2025)
Women’s struggles against patriarchy remain a crucial subject in feminist and postcolonial scholarship, yet limited attention has been given to how cinema contributes to theorizing subaltern subjectivity. This study addresses the gap by analyzing North Country (2005) through feminist criticism and postcolonial theory, particularly Spivak’s concept of the subaltern. The purpose is to examine how women’s silenced voices in patriarchal structures are represented and how subaltern subjectivity transforms into political agency. Using qualitative textual and film analysis, the study integrates Spivak’s subalternity with Butler’s performativity, Foucault’s disciplinary power, Fraser’s redistribution and recognition, and Mohanty’s transnational feminism. Findings show that the mine functions as a patriarchal microcosm, but resistance and solidarity enable women to reclaim voice and agency, redefining the feminist maxim “the personal is political” and extending its resonance transnationally. The study concludes that North Country (2005) is a cultural artifact dramatizing the journey “from subaltern to subject,” underscoring cinema’s role as a theoretical production.